Web GIS-Based Birdwatching Ecotourism Planning in Kwau Village - Reski, Dian; Sumendap, Andreas Leonardo; Dimara, Petrus Abraham (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Ecotourism development in Kwau Tourism Village remains limited due to the absence of systematic spatial mapping and insufficient accessible information regarding bird distribution, despite the area’s rich diversity of endemic species and strong potential for bird-watching activities. The main problem lies in the lack of integrated ecological data that can support informed planning and sustainable ecotourism management. This study offers a solution by combining spatial and non-spatial ecological information to produce a comprehensive decision-support system. The research applies field-based GPS mapping of bird observation points, hotspot analysis, and documentation of temporal behavioral patterns such as feeding and lekking activity. All datasets were processed in ArcGIS and incorporated into an interactive WebGIS platform designed to assist tourism managers, local communities, and visitors in understanding spatial patterns and planning ecotourism activities more effectively. The findings show that bird distribution is concentrated in forest zones with low human disturbance and stable canopy structure, with peak activity occurring in the morning and late afternoon, providing optimal viewing opportunities. Accessibility assessments also indicate that trekking routes vary in difficulty depending on terrain and elevation. Overall, this study contributes a replicable model for GIS-supported bird-based ecotourism that strengthens destination management and enhances visitor preparedness through integrated ecological information.